Working situation and burden of work limitations in sarcoma patients: results from the multi-center prospective PROSa study - Zapata Bonilla, Sergio Armando; Fried, Marius; Singer, Susanne; Hentschel, Leopold; Richter, Stephan; Hohenberger, Peter; Kasper, Bernd; Andreou, Dimosthenis; Pink, Daniel; Arndt, Karin; Bornhäuser, Martin; Schmitt, Jochen; et al. (Journal of cancer research and clinical oncology, 2023)
We investigated predictors of limitations in work performance, odds of drop out of work, and odds of receiving disability pension in sarcoma patients.
Online veröffentlicht: 10. Januar 2023
Gesehen am 28.03.2024